2014
DOI: 10.1002/tox.22073
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effect of the NOS‐mediated oxidative stress in MCF‐7 cells after PbCl2 exposure

Abstract: The potential Pb-induced cytotoxicity in various tissues and biological systems has been reported. Some evidences also indicate that the Pb-caused cytotoxicity may be associated with the nitric oxide synthase (NOS). However, there remains uncertainty about the role of the NOS signaling pathway during the Pb-induced cytotoxicity. In this report, we provide data showing that PbCl2 treatment depresses the expressions of the three distinct NOS isoforms: neuronal nitric oxide synthase (nNOS), endothelial NOS (eNOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…PM2.5 exposure may activate iNOS via reducing its DNA methylation PM2.5 collected from Oct. to Dec. 2015 in Beijing city was analysed, and PM2.5-adsorbed metal elements and polycyclic aromatic hydrocarbons (PAH) were shown in Table 3. Among these components of the PM2.5 in our study, Zn, Ni, Al, Pb and PAHs were all reported to activate iNOS directly [28][29][30][31][32], suggesting the direct activation of iNOS by these PM2.5 components. Especially, PAHs were verified to upregulate iNOS expression via the decrease of their DNA methylation level [33][34][35].…”
Section: The Influence Of Single Exposure To Pm25 On the Level Of Tnmentioning
confidence: 81%
“…PM2.5 exposure may activate iNOS via reducing its DNA methylation PM2.5 collected from Oct. to Dec. 2015 in Beijing city was analysed, and PM2.5-adsorbed metal elements and polycyclic aromatic hydrocarbons (PAH) were shown in Table 3. Among these components of the PM2.5 in our study, Zn, Ni, Al, Pb and PAHs were all reported to activate iNOS directly [28][29][30][31][32], suggesting the direct activation of iNOS by these PM2.5 components. Especially, PAHs were verified to upregulate iNOS expression via the decrease of their DNA methylation level [33][34][35].…”
Section: The Influence Of Single Exposure To Pm25 On the Level Of Tnmentioning
confidence: 81%